Synthesis and characterization of poly(L-lactide-co-ε-caprolactone) (B)-poly(L-lactide) (A) ABA block copolymers - Yodthong Baimark (2018)
ABA triblock copolymers of L-lactide (LL) and ε-caprolactone (CL), designated as PLL-P(LL-co-CL)-PLL, were synthesized via a two-step ring-opening polymerization in bulk using diethylene glycol and stannous octoate as the initiating system. In the first-step reaction, an approximately 50:50mol% P(LL-co-CL) random copolymer (prepolymer) was prepared as the middle (B) block. This was then chain extended in the second-step reaction by terminal block polymerization with more L-lactide. The percentage yields of the triblock copolymers were in excess of 95%. The prepolymers and triblock copolymers were characterized using a combination of dilute-solution viscometry, gel permeation chromatography (GPC), 1H- and 13C-NMR, and differential scanning calorimetry (DSC). It was found that the molecular weight of the prepolymer was controlled primarily by the diethylene glycol concentration. All of the triblock copolymers had molecular weights higher than their respective prepolymers. 13C-NMR analysis confirmed that the prepolymers contained at least some random character and that the triblock copolymers consisted of additional terminal PLL end (A) blocks. From their DSC curves, the triblock copolymers were seen to be semi-crystalline in morphology. Their glass transition, solid-state crystallization, and melting temperature ranges, together with their heats of melting, all increased as the PLL end (A) block length increased. Copyright © 2005 John Wiley & Sons, Ltd.